A death due to a rare form of ligature strangulation - Senathunga, M.M.S.; Hulathduwa, S.R. (Proceedings of CFPSL 14thAnnual Academic Sessions 2016, 2016)
Attached

Garroting is a particular form of asphyxia whereby a restrictive band, cord or other piece of material is placed around the victim’s neck and then tightened manually by means of a stick, rod, pole or other similar object. Case Report A fresh body of a 79 year old male was found in his room with a ligature round his neck and a polyvinyl chkmde(PVC) pipeplaced inside the noose, along with a suicide note. According to the history the deceased was a retired carpenter, who has been bed ridden for more than one year after an accidental fall. He has only taken indigenous medicine and has refused to be treated by doctors. Autopsy revealed a tightly placed ligature horizontally encircling the upper part of the neck, a PVC pipe used for plumbing inserted inside the noose from the back which was twisted several times to further tighten the noose. Marked oedema, congestion, cyanosis and ecchymotic patches were noted above the level of the ligature.The ligature mark was a parchment-like brown coloured stiff imprint abrasion which horizontally encircling the neck.All internal structures in the neck including the hyoid bone, the thyroid cartilages and the cricoidswere normal.Hypostasis fixed on the. posterior aspect of the body except for the pressure points; was noted. All internal organs were normal macroscopically and microscopically. Toxicology reports for alcohol and poisons were negative. Conclusion In the absence of defense injuries, struggle in the scene, poisons and alcohol and in the presence of a suicide note it is more suggestive of suicidal garroting.